Enhanced Right-Chamber Remodeling in Endurance Ultra-Trail Athletes Compared to Marathon Runners Detected by Standard and Speckle-Tracking Echocardiography - Ujka, Kristian; Bastiani, Luca; D'Angelo, Gennaro; Catuzzo, Bruna; Tonacci, Alessandro; Mrakic-Sposta, Simona; Vezzoli, Alessandra; Giardini, Guido; Pratali, Lorenza (Frontiers in Physiology, 2017)
Background: Strenuous and endurance exercise training have been associated with to morphological and functional heart remodeling. Two-dimensional speckle-tracking echocardiography (STE) is a novel technique that allows an accurate quantification of global myocardium deformation. Our aim was to evaluate together left and right cardiac remodeling in different long-distance running athletes: marathon runners (42 km) (M) and endurance mountain runners (> 300 Km) (UT). Methods: A total of 92 athletes (70 males, 76 %) including 47 M (age 45 ± 7 years; training: 18 (9-53) years*days/week), 45 UT (age 42 ± 9, training: 30 (15-66) years*days/week) underwent were submitted to conventional echocardiography and STE (Beyond Diogenes 2.0, AMID) during the agonistic season. Results: Right ventricle (RV) end-diastolic area (p = 0.026), fractional area changing (FAC) (p = 0.008) and RV global longitudinal strain (GLS) were significantly increased in UT athletes. Furthermore, UT showed larger right atrium (RA) volume (p = 0.03), a reduced RA GLS and a significantly increased RA global circumferential strain (GCS) compared to M. After adjustment for age, sex and HR as covariates, UT showed a reduced RA GLS (OR 0.907; CI 0.856-0.961) and increased RV FAC (OR 1.172; CI: 1.044-1.317) compared to M. Conclusion: Athletes enrolled in UT endurance activities showed a RV and RA morphological and functional remodeling to increased preload in comparison with M runners characterized by increased RV FAC and reduced RA GLS. Follow-up studies are needed to better assess the long-term clinical impact of these modifications. 2D STE is a useful tool for to investigatinge the deformation dynamic in different sports specialties.